Management of "frozen shoulder" made easy; critical evaluation on myofascial pain syndrome and conventional orthopedic approaches - Abdul Jalil, Nizar; Prateepavanich, Pradit; Mohamed, Rozilah @ Abdul Hadi (Japan International Cultural Exchange Foundation (JICEF), 2010)
Objective: To evaluate the various coexisting soft tissue pathology that made up "frozen shoulder" and the treatment outcomes. Design: Prospective case series report Methods: All patients with "frozen shoulder"from soft tissue origin were included in this study. A new assessment tool for "frozen shoulder" was performed integrating the conventional orthopaedic approaches with myofascial pain syndrome by performing only three simple range of movement tests; abduction of shoulder joint (Painful Arch Test), external rotation with abducted shoulder joint and Hand On Scapular Blade Test. Results: Fifty percent (50%) of the patients presented with multiple pathology and sixty six percent (66%) of them revealed multiple structures involvement. Prevalence of MPS and tendinitis were equally high in "frozen shoulder" (75%). Seventy five percents (75%) of the patients were successfully managed based on this three steps clinical evaluation. Conclusion: The key success of the "frozen shoulder" management depends on the ability to identify the accurate diagnosis/pathology that made up this complex disorder.